(untitled) (Huellas, 2022)
In 2020 an armed conflict between Armenia and Azerbaijan took place, in an intersection area of the Eurasian space, because of the settlement of Artsakh or Nagorno Karabakh, an area with a majority of Armenian population in the Azerbaijan territory. This interstate territorial controversy affected both Transcaucasian republics and also exposed the interests of the region powers, Russia and Turkey. The purpose of this work is to analyze the role of the Armenian diaspora and their position against the armed conflict, in a threatening context for the region peace. Besides, investigating the historical process allows for the understanding the complex territorial network, the actors involved in it and the bonds that support Armenian identity. This approach is a starting point to do some research on this conflict and to think about the ways to teach it both at a secondary and university level. From the methodological point of view, national and international newspaper articles were analyzed, in which claims, actions and manifestations were described. At the same time, different diasporic group social networks were reviewed to see how they struggled to raise awareness about the genocide at the beginning of the XX century and the resistance to the upcoming conflict.